Determinants of Poverty in the Border Province - Hesti Diah Ayuni; Fariastuti Djafar; Nurul Bariyah (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2026)
Objective: Poverty remains a significant issue requiring attention from local governments, particularly in West Kalimantan. Poverty occurs when a person does not earn enough income to meet their basic needs. This study aims to examine and analyze the effects of economic growth, unemployment, and education on the three indicators of poverty in West Kalimantan. Design/Methods/Approach: The analysis utilizes panel data from 14 districts/cities in West Kalimantan Province, covering the period from 2014-2023. This research employs panel data regression analysis, with the Random Effects Model identified as the optimal model. Findings: The results indicate that economic growth has a positive and significant effect on the three poverty indicators. Unemployment has a positive but insignificant effect on all three poverty indicators. Education has a negative and significant effect on the poverty rate and poverty gap index, but no significant effect on the poverty severity index. Originality/Value: Poverty is often measured by the percentage of people living in poverty, but this approach does not capture the complete picture of poverty experienced by the community. The indicators of the poverty gap index and the poverty severity index can provide a more comprehensive picture because they measure how far the expenditure of the poor is below the poverty line and the inequality in expenditure distribution among them. However, most previous studies have focused on poverty rates, while the use of poverty gap and poverty severity indicators has been limited. Practical/Policy implication: The government should encourage inclusive and sustainable economic growth in West Kalimantan by steering development policies toward equitable access to resources. More effective policies are also needed to address long-term unemployment, such as market-based job training and encouraging investment that can absorb labor. In addition, the West Kalimantan government needs to prioritize education as a primary focus of development, not only in terms of quantity but also in terms of quality and relevance to the labor market’s needs. This is particularly important given the significant role education plays in reducing the three key indicators of poverty.